The Influence of Women’s Political Representation Quotas on Gender-Sensitive Policy Formulation in Local Parliaments in West Sumatra - Rizky, Muhammad (Moccasin Journal De Public Perspective, 2025)
This study examines the influence of women’s political representation quotas on gender-sensitive policy formulation in local parliaments in West Sumatra, Indonesia. While legal quotas have increased the numerical presence of women legislators, their substantive impact on policymaking remains constrained by institutional hierarchies, party dynamics, and cultural norms. Using a qualitative case study approach, data were collected through in-depth interviews with female and male legislators, party officials, and civil society actors, complemented by document analysis of parliamentary reports and local regulations. The findings reveal that women’s participation often remains symbolic, with significant barriers limiting their influence on strategic policy areas. Successful gender-sensitive policies, particularly in maternal health, domestic violence, and education, were achieved primarily through coalition-building, strategic committee engagement, and collaboration with civil society. The study underscores that quotas alone are insufficient to ensure substantive gender equality in policymaking, highlighting the importance of institutional reforms, capacity-building, and cultural change to empower women legislators and promote comprehensive gender-sensitive governance.